Multi-Performance Enhancement of Knitted Wool Fabric with Citric Acid: An Eco-Compatible Cross-Linker. Issue 6 (2nd November 2017) - Raza, Zulfiqar Ali; Siddque, Amna; Mohsin, Muhammad
ABSTRACT: Herein, we report an investigation on an eco-compatible cross-linker, citric acid, to enhance multi-performance characteristics of knitted wool fabric. Citric acid reduced relaxation shrinkage after multiple washings as well as enhanced easy-care performance. Mediation of formic acid as swelling agent further improved cross-linking behavior of citric acid for wool. Shrinkage of wool in course and wale direction after one and five washes were observed, and found that presence of the highest concentration lowered the shrinkage. In addition, crease recovery angle 297°, moisture management 0.675, better dye ability with reactive and acid dye as well as antibacterial activity were achieved at 2% formic acid and 15% citric acid concentrations.